The Propensity for Social Entrepreneurship During the Coronavirus Outbreak - Rita Amelinda, Kartika Nuringsih, Nuryasman MN, (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
This research aims to explore scholarly the propensity for social entrepreneurship (PSE) under the condition of Coronavirus outbreak (Covid-19) and the large scale of social distancing in Jakarta, Indonesia. Entrepreneurial education is expected to encourage awareness of social problems among students. This research examines the relationship between perceived social supports and PSE. Additionally, it investigates the mediating effect of self-efficacy that links among empathy, moral obligation, and prior experience towards PSE. As many as 180 students filled the questionnaire through google forms during April 22-29th 2020. By using Smart-PLS proves a significant effect of perceived social support toward PSE and discovers the mediation effect on social entrepreneurial self-efficacy. The result shows a positive mindset on social entrepreneurship among students whereas this pandemic is as a trigger to intent in social entrepreneurship. It is a mechanism when understanding the social entrepreneurial education for students, thus leaders can utilize to improve regulation in the entrepreneurship learning program.